Retrospective Review of Pyrocarbon Hemiarthroplasty for Carpometacarpal Arthritis: An Examination of Long-Term Outcomes and Complications - Rode, Matthew M.; Mullen, Barbara L.; Schrader, Samuel N.; Rizzo, Marco; Moran, Steven L. (Journal of Wrist Surgery, 2025)
Thumb carpometacarpal (CMC) arthritis is a common and sometimes debilitating condition with a variety of surgical treatments. Pyrocarbon thumb CMC hemiarthroplasty is one option, which has demonstrated promise; however, no long-term outcomes have been reported.We performed a retrospective institutional review of 106 primary thumb CMC pyrocarbon hemiarthroplasties with a minimum of 1 year, median 6.1-year follow-up. We analyzed rates of pain relief, reoperation, and implant failure as well as biomechanical, radiographic, and patient-reported outcomes.Pain was significantly decreased after surgery. Radial and palmar abduction were modestly improved postoperatively (increased from 40–50 degrees). Implants showed high rates of radiographic osteolysis (53%) and subsidence (44%). Two-, 5-, and 10-year rates of reoperation (18, 21, 21%) and implant removal (15, 19, and 19%), respectively.Pyrocarbon thumb CMC hemiarthroplasty provides high rates of pain relief and preservation of pinch and grip strength. Patients had modest improvement in radial and palmar abduction; however, hemiarthroplasty was associated with moderate rates of reoperation and implant revision.Therapy Level IV.
Keywords: carpometacarpal arthritis; pyrocarbon; arthroplasty; patient-reported outcomes